2021
DOI: 10.1096/fj.201802376rrrr
|View full text |Cite
|
Sign up to set email alerts
|

An improved in vitro model for studying the structural and functional properties of the endothelial glycocalyx in arteries, capillaries and veins

Abstract: The endothelial glycocalyx is a dynamic structure integral to blood vessel hemodynamics and capable of tightly regulating a range of biological processes (ie, innate immunity, inflammation, and coagulation) through dynamic changes in its composition of the brush structure. Evaluating the specific roles of the endothelial glycocalyx under a range of pathophysiologic conditions has been a challenge in vitro as it is difficult to generate functional glycocalyces using commonly employed 2D cell culture models. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 79 publications
(199 reference statements)
0
14
0
Order By: Relevance
“…Therefore, we additionally performed a native thickness determination using WGA, verifying our aforementioned results ( Supplementary Figures S4, S5 ). When analyzing the glycocalyx composition and potential changes induced by fluid flow we found a slightly increased amount of uniformly distributed CS on HUVECs after dynamic culture ( Figure 3 ), which is somewhat surprising as CS is not a typical mechanosensor ( Pahakis et al, 2007 ; Siren et al, 2021 ). Nevertheless, also Zeng and Tarbell (2014) found an upregulation of CS after dynamic culture of bovine aortic ECs with a uniform CS distribution.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, we additionally performed a native thickness determination using WGA, verifying our aforementioned results ( Supplementary Figures S4, S5 ). When analyzing the glycocalyx composition and potential changes induced by fluid flow we found a slightly increased amount of uniformly distributed CS on HUVECs after dynamic culture ( Figure 3 ), which is somewhat surprising as CS is not a typical mechanosensor ( Pahakis et al, 2007 ; Siren et al, 2021 ). Nevertheless, also Zeng and Tarbell (2014) found an upregulation of CS after dynamic culture of bovine aortic ECs with a uniform CS distribution.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the comparison of glycocalyx status after static and dynamic culture is important, as it has been shown before that, for example, glycocalyx thickness is highly dependent on applied fluid flow in in vitro studies ( Ueda et al, 2004 ; Gouverneur et al, 2006b ; Siren et al, 2021 ). In our present study we also found a significantly higher glycocalyx layer thickness after dynamic culture with ∼2 µm for HUVECs and ∼2.5 µm for iPSC-ECs ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most clinical studies have measured SDC-1 as a marker of EG shedding as the predominant syndecan shed into the blood of critically unwell patients is SDC-1 and -3, and SDC-4 and SDC-2 levels are not significantly elevated compared to healthy controls [34]. SDC-1 cell surface expression is upregulated in response to shear stress [11,35,36], and this downregulates the expression of SDC-4 via cell signalling pathways [37], but not vice versa. Instead, SDC-4 upregulation appears to be a compensatory response to the decreased expression of SDC-1 [37].…”
Section: Limitations Of the Modelmentioning
confidence: 99%
“…There are also other differences between endothelial cells cultured under flow compared to static conditions. There is a linear relationship between shear stress and the rate of EG growth [36,39,40]. Higher shear stress conditions result in increased expression of hyaluronan [35,36], intracellular adhesion molecule 1 (ICAM-1) [36,40], and von Willebrand Factor [36].…”
Section: Limitations Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation